ANALYSIS OF THE APPLICATION OF INTERNATIONAL TAX TREATIES (Academicia Globe: Inderscience Research, 2024)
In this article, in the context of the active development of the Republic of Uzbekistan and the processes of globalization in the world economy, the constantly growing mobility of international investment resources, actively contributing to the development of the capital market, such tasks are set for all countries. Scientific proposals and recommendations have been developed for the creation of national tax legislation, which not only ensures the investment attractiveness of the national economy for foreign capital, but also allows the tax authorities to ensure tax revenues in full and on time.